PENGELOLAAN INSTAGRAM X GROUP DALAM UPAYA MENINGKATKAN EMPLOYEE ENGAGEMENT KARYAWAN - Novy Rojali (Fakultas Dakwah dan Komunikasi, 2021)
This study aims to determine and describe the management of Instagram media for employee engagement X Group in increasing employee engagement. To achieve these objectives, the authors use descriptive and qualitative research methods through a case study approach. The results showed that various features of X Group's Instagram employee engagement have been used to support interactions between companies and employees and among employees. The management of Instagram media has succeeded in making employees feel proud, motivated, and excited at work, even though situations where employees feel at home and will not be separated from their work are still not visible.